Social Studies of Technology: Evolution and Interaction of Approaches - Liliia Zemnukhova (Journal of Economic Sociology, 2018)
Digital technologies are being introduced into the practice of users and are being encountered with multiple barriers on their way. The process of production and diffusion of technology and innova-tions is the focus of attention in two disciplinary areas—innovation studies (IS) and science and technology studies (STS). The early IS focused on the diffusion of innovation, revising its model-ing from a linear to an interactive perspective: they based studies on quantitative data and took in-to account institutional interactions. STS as an umbrella of social studies of technology and tech-noscience suggested several diverse approaches for identifying the main strains and obstacles in this process. For example, the area that has become known as social construction of technology (SCOT) focused on the role of users and groups in the production and development of technolo-gies, based on the reciprocity of their interaction (Trevor Pinch; Wiebe Bijker). Representatives of actor-network theory (ANT) developed the concepts of socio-technical systems and frames to reveal the details of the use and “travel” of technical objects in complex networks of relations (Madeleine Akrich; Patrice Flichy). At the intersections of IS and STS, more complex models and concepts are born, such as socio-technical configurations, where social relations give meaning to technological artifacts (Arie Rip, René Kemp). This review presents both examples of classic works in the mentioned disciplinary areas and specific attempts to conceptualize the socio-technical aspects of the diffusion of innovation.